Diferentes sons e tons em aulas de matemática: um estudo sobre frações - Rocha, Ezequiel Ribeiro (Universidade Federal de São Carlos, 2022)
The present work aims to analyze the context of being a teacher and inquirer of one's own practices in the scope of mathematics education in elementary school, which presumes to find conceptions formed by experiences of knowledge that are generally constituted of skills and competences through a continuous educational formation. The descriptive qualitative research seeks to contextualize reflections on forms of interdisciplinary representations between art, that is, the "analog and digital temperament" and mathematics, comprising fractions in forms of sequences and applications, aimed at the teaching-learning process, in the ludic context of fractions and music, tied by challenges in diverse environments and moments of a before, during, and the delicate progressive return to physical school spaces, due to the pandemic unfolding of Covid-19. Thus, this work emerges from the essence of the theoretical referential of youth and adult education pronounced by FREIRE (1970, 1991, 1993, 1997), having music as the generating element of the reflections of the research scope. Together with the students, dynamics occur followed by planned evaluative activities that make it possible to work, firstly, numbers and decimal fractions, exact square roots, functions, incomplete trinomials as bold contextualized and applied interventions related to the proposed interdisciplinarity. In the path paved by the theoretical reference, relations are established with the ideas proposed by Cury (2008), a support of "error analysis" hypothetically during the study that followed students in continuity from 6th to 8th grade in the city of Vinhedo, two 8th grades and one 9th grade, as a form of adjustment, acceleration, content correction and curriculum of students from a Municipal school of Monte Mor. Furthermore, interpersonal pedagogical relationships and the virtual pedagogical dynamics were compared to the third face-to-face bias of applying the dynamics based on the scope of fractions and (in) music in 2022. Age issues in school years, behavioral issues, gaps and mismatches, (dis)organization of actions as well as hidden curricula of an elementary mathematics baggage, are some of the variables manifested in the empirical forms of belief segments that occurred in both agents of predominant performances: educator and students.
Different sounds and tones in math classes: a study about fractions
Keywords: Processo ensino-aprendizagem; Ensino analógico e digital; Música e matemática; Frações e(m) música; Teaching-learning process; Analog and digital teaching; Music and mathematics; Fractions and(in) music; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::TECNOLOGIA EDUCACIONAL